2019
DOI: 10.1111/cxo.12851
|View full text |Cite
|
Sign up to set email alerts
|

Ocular and visual discomfort associated with smartphones, tablets and computers: what we do and do not know

Abstract: Smartphone and tablet use in Australia and worldwide is reaching saturation levels and associated visual and ocular discomfort such as headaches, eyestrain, dry eyes and sore eyes are widespread. This review synthesises the available literature and considers these symptoms in the context of a binocular vision and/or ocular surface aetiology. Eye discomfort with smartphones and tablets is discussed alongside similar symptoms reported with desktop computer use. Handheld devices differ from computers in viewing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
195
1
16

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(257 citation statements)
references
References 67 publications
(161 reference statements)
10
195
1
16
Order By: Relevance
“…3 Prolonged usage of handheld digital devices, like smart phones, computers, may adversely impact tear stability and this can lead do adverse complications such as dry eye. 5 Literature from Asian countries like Japan studies reported that nearly (18.6%) of the females and (30%) of the males reported dry eyes following computer use. In contrast, to observed symptoms of dry eyes in (10.1%) of male and (21.5%) of female Japanese workers using VDTs at office work.…”
Section: Discussionmentioning
confidence: 99%
“…3 Prolonged usage of handheld digital devices, like smart phones, computers, may adversely impact tear stability and this can lead do adverse complications such as dry eye. 5 Literature from Asian countries like Japan studies reported that nearly (18.6%) of the females and (30%) of the males reported dry eyes following computer use. In contrast, to observed symptoms of dry eyes in (10.1%) of male and (21.5%) of female Japanese workers using VDTs at office work.…”
Section: Discussionmentioning
confidence: 99%
“…The issues that were reported were related either to with prolonged nearterm adaptation (i.e., blurred vision at close range, difficulty in focusing, and copious headache after screen use) and those related to dry eye syndrome (irritation/burning sensation, ocular fatigue, discomfort, photosensitivity), while symptoms due to poor posture and prolonged physical immobilization in front of the screen (such as neck pain, tension headache, and other atypical musculoskeletal pain) are also very common. Preexisting vision problems (hyperopia / myopia, astigmatism, and adaptive disorders) can contribute to the appearance of the syndrome if they are not adequately addressed or have not yet been diagnosed (9,10).…”
Section: Negative Effects Of Videogaming Problematic Internet Use Amentioning
confidence: 99%
“…There is very little literature reporting the effect of digital device use on the vision and ocular health of children and teenagers [39], despite reports that children as young as 2 years use digital devices [40]. Associations have been reported between smartphone/computer use and dry eye in children [41] (see section 2.7 below).…”
Section: Children and Youthmentioning
confidence: 99%
“…There also appears to be an association with hours of smartphone / computer use and dry eye in children [41] but this work only reports total hours use per day, not continuous use. The impact of intermittent device use and multiple device use on visual comfort and ocular health and the maximum recommended use time requires further investigation [21,39].…”
Section: Rest Breaksmentioning
confidence: 99%